Constitutionality of Replacing Judges Mid-Term and Its Implications on the Independence of the Constitutional Court, Indonesia - Hayya, Nur Mila; _, Rosmini; Nugraha, Harry Setya (As-Siyasi: Journal of Constitutional Law, 2023)
This research examines the legal problems surrounding the dismissal of Aswanto as a judge of the Constitutional Court of the Republic of Indonesia (MKRI), where the dismissal is deemed inconsistent with the prevailing laws and regulations. This study employs a doctrinal research type with a normative juridical approach through the examination of legislation and conceptual understanding to scrutinise the constitutionality of the replacement of constitutional judge Aswanto by the People's Representative Council (DPR) and its implications on the independence of the Constitutional Court. The findings suggest that, firstly, the replacement of Judge Aswanto during his tenure by the DPR is an unconstitutional act as it does not align with the constitution. Secondly, this replacement has implications for weakening the independence of the Constitutional Court, including constitutional independence, functional independence, personal independence, and evident practical independence. Therefore, the President needs to annul Presidential Decree Number 114/P/2022 and restore Judge Aswanto to his original position. Additionally, to prevent the misuse of power, further limitations and elaborations are required regarding the DPR's supervisory function over the judiciary, in this case, the Constitutional Court, in accordance with the system of checks and balances.